TRAINING CLASSES IN THE INCOME TAX UNIT. - Beers, J. W. (The Accounting Review, 1928)
Back in 1917 and 1918 at the time that invested capital propositions were worrying the taxpayer, the country was full of clerks who thought they were bookkeepers; it was also full of bookkeepers who thought they were accountants; and then there were a number of actual, honest-to-goodness accountants, but the number was limited. The U.S. Internal Revenue Bureau needed accountants and many of them. The real accountants were already employed in the commercial world at salaries, which did not make government stipends look alluring to them. Some very able accountants came into the service but the number of those that came was so small compared to the needs that something had to be done to augment the force of accountants quickly. The income tax law as it was framed in 1917 and 1918 brought into existence a new profession. Proficiency in this new profession required knowledge of two subjects-accounting and tax law, and the two had to be merged. It not only required knowledge of accounting but it required knowledge of accounting from the viewpoint of the tax law and the Treasury Department. To create members of this new profession was the work of the Training Section.